HUBUNGAN MOTIVASI DENGAN IMPLEMENTASI KOMUNIKASI SBAR DALAM TIMBANG TERIMA PERAWAT PADA SEBUAH RUMAH SAKIT DI BALI - Dewi, Ni Putu Santika; Sri Krisnawati, Komang Menik; Yanti, Ni Putu Emy Darma (Coping: Community of Publishing in Nursing; Vol 12 No 3 (2024): Juni 2024DO - 10.24843/coping.2024.v12.i03.p05, 2024)
Situation, background, assessment, recommendation (SBAR) communication is an effective communication that is appropriate to use in comprehensively conveying the patient's condition. The successful implementation of SBAR communication is one way to achieve quality service quality so that medical personnel who have high performance and motivation are needed. This study aims to determine the relationship between motivation and the implementation of SBAR communication in receiving nurses at the Bali Mandara Regional General Hospital. This study uses a correlative quantitative method with a cross sectional approach. Sampling was carried out using simple random sampling and stratified random sampling techniques with a total of 84 nurses who gave operands at handover in the cempaka, sandat, and cassowary rooms. Data collection was carried out using a questionnaire to measure motivation and an observation sheet to measure the implementation of SBAR communication at the time of weighing of nurses who have been tested valid and reliable. The analytical test used is the Spearman rank correlation test with a 95% confidence level. The results of the analysis test using spearman rank showed that there was a relationship between motivation and the implementation of SBAR communication in nurse's handover (p-value = 0,009). It can be concluded that motivation is related to the implementation of SBAR communication where the higher the level of motivation, the higher the implementation of SBAR communication by nurses.